LEGAL NATURE OF CORPORATE AGREEMENTS - Рябова, Катерина Олексіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the article is devoted to the analysis of the legal nature of corporate contracts and agreements between shareholders; their subject is a circle of subjects. Research methods: analyzed the approaches of various scholars regarding the definition of the concept of «corporate contract», as well as the norms of current legislation governing the legal relations arising from the conclusion of contracts of this type. The results: revealed the economic and legal nature of legal relations arising from the conclusion of contracts of this type. Discussion: of the problems of domestic legislation and practice, there are entering into corporate contracts. The main idea of the article is the understanding of the concept and legal nature of the corporate agreement. The variability of the opinions of scholars led to a heated discussion in the scientific and legal literature: some researchers consider such a contract quite widely, including a large range of issues for its subject; other scholars substantiate the highly specialized understanding of the corporate contract as agreements only on the management of corporate rights. Regarding the legal nature, there are also different opinions. Some even equate the corporate agreement with the joint venture agreements, and the limits of the agreements of the owners of corporate rights are defined as depriving these owners of the opportunity to change the general public order, established in the charter and, to a certain extent, in the founding agreement. Such an opinion is due to the analysis of the subject of corporate agreements, which stipulates the implementation of the joint coordinated activity of its participants, ie joint management of corporate rights. The author comes to the conclusion that the оn the basis of the analysis of current legislation and judicial practice, we can draw a conclusion on the economic and legal nature of corporate agreements. Although the corporate agreement and the agreement between the shareholders are subject to different legal regulation, they still show a sufficient similarity. A deep analysis of the rules of law gives an opportunity to draw a conclusion on the identity of concepts. Further theoretical advances are needed regarding the possibility of distinguishing the notion of a corporate agreement as a general category, and a contract between shareholders as a special one, which will entail the necessity of making the corresponding changes in the current legislation.